Biomechanical Comparison of Three Crural Fascia Repair Techniques for Tibial Tuberosity Advancement Surgery - Giangarra, Jenna E.; Lanz, Otto I.; Glennon, Joseph C.; Kobayashi, Takayuki; Tarkanian, Michael; Tepic, Slobodan; Werre, Stephen R. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objectives The aim of this study was to compare the strength of three described techniques for repair of the medial crural fascia to the strength of the intact fascia of the paired limbs. We hypothesized that intact controls would have higher peak loads at failure than repair groups and that the modified Mason–Allen suture pattern would have the highest peak load at failure of the repair groups.Materials and Methods Canine cadavers (n = 22) were randomly assorted into three groups. Group A: a continuous suture pattern. Group B: five equally spaced simple interrupted cruciate sutures over a simple continuous suture pattern. Group C: an interrupted modified Mason–Allen suture pattern. The mid-portion of the crural fascia was incised in Groups A and C, while Group B used a cranial incision. Contralateral limbs were utilized as paired controls. Tibiae were mounted to a biomaterial testing machine and the medial crural fascia loaded at 10 mm/min.Results Mean peak load to failure for Group A: 201.0N, Group B: 261.0N, Group C: 306.1N and Intact limbs: 799.5N. Between repair groups, there was no significant difference between peak loads to failure identified. Significant differences were identified between all repairs and intact limbs. All repairs approached a mean of 33.5% (267.8N) of intact medial crural fascia strength.Clinical Significance All repair techniques met no more than 1/3 intact medial crural fascia strength. Further research is required to continue to evaluate the most clinically appropriate technique to repair the medial tibial crural fascia.
Keywords: repair; crural fascia; biomechanical comparison; tibial tuberosity advancement; canine